A Matter of Time: Variations in High School Course-Taking by Years-as-EL Subgroup. (December 2019) - Johnson, Angela
English learners (ELs) lag behind their peers in academic achievement and attainment, partly due to limited exposure to academic content. Prior studies that examine high school course-taking find significant course access gaps between ELs and non-ELs but provide little information on the relation between course-taking and time spent as an EL. This study improves upon previous research by addressing this dimension of heterogeneity and reporting detailed by-subject analyses. I use student-level data (N = 41, 343) from a unique district in California with a large number of Chinese and Spanish ELs. I find substantial heterogeneity in general and advanced course-taking based on time spent as an EL. But differences disappear once eighth grade test scores are taken into consideration.